Interrelationships between changes in erythropoietin, plasma volume, haemoglobin concentration, and total haemoglobin mass in endurance athletes. Issue 3 (3rd July 2018) - Sitkowski, Dariusz; Szygula, Zbigniew; Pokrywka, Andrzej; Turowski, Dariusz; Malczewska-Lenczowska, Jadwiga
ABSTRACT: Interrelationships between physiological changes (Δ) in erythropoietin (EPO), plasma volume (PV), haemoglobin concentration ([Hb]), and total haemoglobin mass (tHb-mass) were examined in cyclists who trained in different altitudes. Regardless of differences in pattern of changes observed in three training locations, ΔEPO was correlated positively with ΔPV, negatively with Δ[Hb], and trivially with ΔtHb-mass. Δ[Hb] was negatively correlated with ΔPV. In the pooled data the Spearman's rank correlation coefficients were as follows: r = 0.783, P < 0.001; r = −0.704, P < 0.001; r = 0.136, P > 0.05; r = −0.813, P < 0.001, respectively. The obtained results have shown that EPO does not only regulate [Hb] by erythropoiesis stimulation but also by PV modulation, which probably aims at keeping proper level of arterial oxygen content for oxygen delivery to tissues.